Inteligenţa artificială la graniţa dintre forma benignă de abstractizare şi conotaţia incertitudinilor ameninţătoare /Artificial Intelligence at the Border between the Benign of Abstraction and the Connotation of Threatening Uncertainties - Mădălina-Gabriela GUŢĂ; Ruxandra GOROVEI (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice)
Today, the hierarchies of technology have become palpable realities, re-establishing the boundaries of humanity through the existence of robots, apps or programmes that replace dangerous or repetitive human labour, facilitating people's daily activities. We wonder whether (or not) this technological development leads us only to positive aspects. Artificial intelligence requires an extensive process of legislative codification in a flexible manner which does not diminish its functionality, but which is precise and secure enough to protect those who entrust it with their trust.